2015
DOI: 10.3390/ma8041526
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Binding of Heparin to Functionalized PET Materials for Improved Haemocompatibility

Abstract: The hemocompatibility of vascular grafts made from poly(ethylene terephthalate) (PET) is insufficient due to the rapid adhesion and activation of blood platelets that occur upon incubation with whole blood. PET polymer was treated with NHx radicals created by passing ammonia through gaseous plasma formed by a microwave discharge, which allowed for functionalization with amino groups. X-ray photoelectron spectroscopy characterization using derivatization with 4-chlorobenzaldehyde indicated that approximately 4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…To overcome this challenge, heparin, a widely used anticoagulant biopolymer, has been used in numerous vascular engineering applications 8, 23, 35, 36, 50 . To achieve the desired outcome, the heparin must exist at the blood-material interface in an adequate dose for a sufficient period.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this challenge, heparin, a widely used anticoagulant biopolymer, has been used in numerous vascular engineering applications 8, 23, 35, 36, 50 . To achieve the desired outcome, the heparin must exist at the blood-material interface in an adequate dose for a sufficient period.…”
Section: Resultsmentioning
confidence: 99%
“…An appealing explanation is that the majority of heparin (which is presented on the polymer before incubating with fresh blood; see Table 1) is removed upon incubation. Namely, bonded heparin always prevents any adhesion and activation of blood platelets on the surface of PET polymer [8]. It is interesting that the concentration of blood platelets on the surface of samples treated by O-atoms and subsequently incubated with heparin appears to be even larger than on the samples treated only by oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…They either can interact chemically with blood constituents or are just dissolved and washed away. Although numerous attempts have been made to stabilize such coatings on polymer surfaces, the results are still not optimal [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Modic et al studied platelet adhesion on surfaces treated in pure oxygen plasma and found these surfaces to have excellent hemocompatibility properties . In contrast, Kolar et al and Primc et al studied the influence of nitrogen and ammonia plasma treatment on platelet adhesion and found worse hemocompatibility in comparison with that produced by oxygen plasma treatment . However, the hemocompatibility of surfaces treated in nitrogen and ammonia plasma still appears to be better than that produced by SO 2 or H 2 S plasma treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In the first case, various plasmas have been already used, such as oxygen, CO 2 , argon, ammonia and nitrogen plasmas, for improving cell adhesion and proliferation . In the case of improving hemocompatibility properties of vascular grafts, plasma is normally used only as an initial step to enable further surface grafting with specific molecules that have antithrombogenic properties . Nevertheless, it has also been shown that a remarkable decrease in platelet adhesion can be obtained by using solely an oxygen plasma treatment …”
Section: Introductionmentioning
confidence: 99%